Dinamika Legalisasi Tanah Desa di Kabupaten Sleman, Yogyakarta: Pengaturan, Pelaksanaan, dan Implikasinya - Prasetya, Dimas Bayu Candra; Mujiburohman, Dian Aries; Supama, Yohanes (Widya Bhumi, 2024)
Legal uncertainty in the legalization of village land in DIY arises from differences between national and regional regulations. This study examines the legalization of village land in Sleman, Yogyakarta, from the aspects of regulation, implementation, and its implications. The research method employed is a normative-empirical legal analysis focusing on regulations related to village land and their ontological basis. The findings show that the regulation of village land in the Special Region of Yogyakarta (DIY) has undergone changes since the pre-independence era, during which land was under the authority of the Kasultanan and Pakualaman with limited usage rights. After independence, DIY gained special rights in agrarian management, reinforced by the DIY Privileges Law (UUK). However, the implementation of the Basic Agrarian Law (UUPA) in DIY was delayed until 1984. Significant changes in village land regulations, from the 2008 to 2024 Governor’s Regulations, reveal inconsistencies with national land laws and the Village Law. This creates challenges in legal synchronization, where the UUK, as lex specialis, may lead to legal uncertainty in the legalization and certification of village land. These findings provide valuable input for policy development to strengthen the legal framework for village land and improve community welfare through better land management. Ketidakpastian hukum dalam legalisasi tanah desa di DIY timbul dari perbedaan pengaturan nasional dan daerah. Penelitian ini mengkaji legalisasi tanah desa di Sleman, Yogyakarta, dari aspek pengaturan, pelaksanaan, dan implikasinya. Metode yang digunakan adalah yuridis normatif-empiris dengan analisis terhadap peraturan terkait tanah desa dan dasar ontologis penetapannya. Hasil penelitian menunjukkan bahwa pengaturan tanah desa di Daerah Istimewa Yogyakarta (DIY) telah mengalami perubahan sejak masa pra-kemerdekaan, di mana tanah berada di bawah otoritas Kasultanan dan Pakualaman dengan hak pakai terbatas. Setelah kemerdekaan, DIY memperoleh hak istimewa dalam pengaturan agraria, diperkuat oleh Undang-Undang Keistimewaan DIY (UUK DIY). Namun, implementasi Undang-Undang Pokok Agraria (UUPA) di DIY baru terlaksana pada 1984. Peraturan tanah desa mengalami perubahan signifikan dari Peraturan Gubernur DIY tahun 2008 hingga 2024, mencerminkan ketidaksesuaian dengan hukum nasional dan Undang-Undang Desa. Hal ini menimbulkan tantangan dalam sinkronisasi hukum, di mana UUK DIY sebagai lex specialis berpotensi menimbulkan ketidakpastian hukum dalam legalisasi dan sertifikasi tanah desa. Temuan ini memberikan masukan bagi kebijakan untuk memperkuat kerangka hukum tanah desa dan meningkatkan kesejahteraan masyarakat melalui pengelolaan tanah yang lebih baik.